Eleanor Vadala and Dr. Earl Hayes at the Naval Air Material Center - United States. Navy; Naval Air Engineering Center (U.S.) (1959)
Eleanor Vadala, chemist, and Dr. Earl Hayes, U.S. Defense Department, examining a display of airship fabric produced at the Naval Air Material Center. Ms. Vadala demonstrates the threads on an airship model while Dr. Hayes looks on. Several wall displays highlighting the rubber and textile branches of the Aeronautical Materials Laboratory's High Polymer Division are also visible.
Keywords: Women in science; Aerospace Research Laboratories (U.S.); Airships--Design and construction; Airships; Polymers; Women chemists; Naval Air Engineering Center (U.S.); Chemists; Vadala, Eleanor, 1923-